A Story Told Twice - Pavičić, Davor (Dějiny – teorie – kritika, 2021)
One of the prominent guests at the opening ceremony of the Suez Canal in 1869 was the Austro-Hungarian Emperor Franz Joseph, in whose entourage was a Czech-born priest Beda Dudík, entrusted with writing an official travelogue about the Emperor’s trip. Ten years later, his younger brother Antonín published his own version of the travelogue in Czech, based on his brother’s travelogue and experience. This article compares and contextualizes the two travelogues which describe the same events but were written by two brothers in different languages, for different audiences and from different perspectives. In addition to giving a new insight into the lives of the two Dudík brothers and the Emperor’s trip to the East, emphasizing personal experience and reflections of Austro-Hungarian citizens in a world different from their own, the article focuses on the so far largely unknown travelogue written by Antonín Dudík. Details and tools which distinguish the tone of Antonín’s travelogue from that of his older brother Beda reveal nuanced differences in the two narratives, which convey different messages to their intended audiences.